Psycholinguistic Perspectives on Language Maintenance in Children: Cognitive and Affective Factors - Ikram Senen (Winaya Inspirasi Nusantara Foundation, 2022)
The erosion of regional and minority languages among youth has emerged as a significant issue in multilingual society, especially where prevailing national or global languages eclipse local linguistic traditions. This study seeks to rigorously analyze the psycholinguistic aspects of language maintenance, emphasizing the interplay between internal mechanisms such as working memory, phonological awareness, and motivation, and external factors like input quality and social context in influencing children's retention of their heritage language. This study utilizes a critical review methodology to synthesize data from peer-reviewed studies published in high-impact journals from 2010 to 2022, focusing on psycholinguistics, bilingualism, and language acquisition. The approach delineates four principal themes: cognitive retention mechanisms, the significance of consistent and emotionally resonant input, affective and motivating factors, and the critical function of sociocognitive interactional situations. The results indicate that language maintenance is a dynamic, multimodal process shaped by individual cognitive abilities and the emotional and social contexts of language usage. These results necessitate the development of more comprehensive theoretical models and context-specific therapies that consider both linguistic exposure and the cognitive and emotional experiences of young language users. The research enhances comprehension of language sustainability and provides actionable insights for educators, families, and policymakers involved in language revitalization initiatives.